2014
DOI: 10.3892/ol.2014.2012
|View full text |Cite
|
Sign up to set email alerts
|

Primary retroperitoneal extraskeletal mesenchymal chondrosarcoma involving the vena cava: A case report

Abstract: The current study presents a case of extraskeletal mesenchymal chondrosarcoma (ESMC) involving the vena cava that originally occurred in the retroperitoneum of a 61-year-old female. Following excision of the masses, pathological examination confirmed a diagnosis of primary ESMC. Mesenchymal chondrosarcomas are extremely rare in comparison to conventional chondrosarcomas and even more so when arising in an extraskeletal location. In the current report, the major characteristics of ESMC are discussed and a revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…The most common sites of origin are long limbs, orbital wall, and rarely spinal meninges. It has also been reported in axillary and shoulder region as isolated case reports [1, 3,4] . ESMCS is a very rare pathologic entity with no specific clinical or radiologic characteristics to distinguish them from other neoplastic pathologies.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The most common sites of origin are long limbs, orbital wall, and rarely spinal meninges. It has also been reported in axillary and shoulder region as isolated case reports [1, 3,4] . ESMCS is a very rare pathologic entity with no specific clinical or radiologic characteristics to distinguish them from other neoplastic pathologies.…”
Section: Discussionmentioning
confidence: 97%
“…ESMCS is a rare neoplasm first described in clinical literature in 1959 by Lichenstein and Berstein [3,4] . There are 2 histological variants, mesenchymal and myxoid, out of which former is rarer, more aggressive, and carries poorer prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ESMC may appear in any location that contains mesenchymal cells; primary sites include limb extremities, the torso, the head and neck, and rarely the heart (23)(24)(25). Compared with the myxoid subtype, the ESMC subtype is rare, more aggressive and with poor prognosis due to the high probability of metastases (26), which may occur several years following the initial treatment. Cardiac metastasis of ESMCs is infrequent; it has been reported that the most common site of cardiac metastasis are the right atrium and left intracavity, leading to pulmonary embolism and systemic embolism (27,28).…”
Section: Discussionmentioning
confidence: 99%